An empirical analysis of green switching intentions in the airline industry. Issue 8 (3rd July 2018) - Wu, Hung-Che; Cheng, Ching-Chan; Ai, Chi-Han
Abstract : The purpose of this research is to gain an empirical understanding of airline passengers' green switching intentions. A conceptual research model is used as a framework to examine the relationships among the experiential quality dimensions, green perceived value, green corporate image, green experiential satisfaction, green corporate reputation, green experiential loyalty and green switching intentions for the airline industry. The data used in this paper were based on a sample of 615 passengers who experienced the eco-friendly services of China Airlines, indicating that the proposed model fitted the data. The study's result will assist airline management to develop and implement market-orientated service strategies to increase the experiential quality dimensions, green perceived value, green corporate image, green experiential satisfaction, green corporate reputation and green experiential loyalty in order to decrease passengers' green switching intentions.